Mobility-enhanced thermoelectric performance in textured nanograin Bi2Se3, effect on scattering and surface-like transport - Bayesteh, Samaneh; Sailler, Sebastian; Schlörb, Heike; He, Ran; Schierning, Gabi; Nielsch, Kornelius; Pérez, Nicolás (Materials Today Physics, 2022)
We report on the effect of artificially generated textures of Bi2Se3 in thermoelectric performance and low-temperature magnetoresistance. A set of texturized nanograined Bi2Se3 samples was investigated, ranging from predominantly c-axis texture to random texture. c-axis oriented layered domains rendered the samples highly conducting due to drastically enhanced mobility, up to 1600 cm2V−1s−1 at low temperature, and enhanced both carrier concentration and electrical conductivity. The largest power factor of 800 μWm−1K−2 and highest zT≈ 0.14 both at 300K were observed in a sample with a predominantly layered and c-axis oriented texture. The random texture reduced the thermal conductivity, while the Seebeck coefficient showed no particular correlation with the texture. We have shown that the milling procedure generated a higher degree of disorder by increasing the milling frequency. As a result, the carrier scattering mechanism in the samples changed from mostly electron-phonon interaction at 5Hz to disorder-related scattering at 10Hz and 20Hz milling frequency. The weak antilocalization effect was observed in the magnetoresistance of pressed samples with different textures, pointing towards surface-like transport channels. The Hikami-Larkin-Nagaoka (HLN) model was used to evaluate the phase coherence length, resulting in a high value of roughly 600 nm regardless of the texture. However, a larger number of surface-like transport channels was obtained for the samples with random texture.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Ball milling; Bi; Scattering; Thermoelectricity; Topological insulators